Systematic mapping on social media and its relation to business - Carolina Nicolas Alarcón; Angélica Urrutia Sepúlveda; Leslier Valenzuela-Fernández; Jaime Gil-Lafuente (European Research on Management and Business Economics (ERMBE), 2018)
The aim of this study is to analyse the reach of existing investigation on social media and its relation to companies throughout 2014–2015. To achieve the proposed, the study proceeds in classifying such information and identifying methods to study social media and it's relation with different marketing associated topics. The research uses a mapping process that uses the database generated from references of Web of Science's publications during 2014–2015, amounting to 185 articles. The results found that the initial method is a descriptive analysis on the usage of social media as a tool for marketing. Nevertheless, during the past years studies have proposed that social media is becoming more an instrument for marketing and business management.
Keywords: M31; 650; Systematic mapping; Social media; Internet; Business; Twitter